2016
DOI: 10.1155/2016/1957374
|View full text |Cite
|
Sign up to set email alerts
|

The Association between NOS3 Gene Polymorphisms and Hypoxic-Ischemic Encephalopathy Susceptibility and Symptoms in Chinese Han Population

Abstract: Endothelial NOS (NOS3) has a potential role in the prevention of neuronal injury in hypoxic-ischemic encephalopathy (HIE). Thus, we aimed to explore the association between NOS3 gene polymorphisms and HIE susceptibility and symptoms in a Chinese Han population. Three single nucleotide polymorphisms (SNPs) in the NOS3 gene, rs1800783, rs1800779, and rs2070744, were detected in 226 children with HIE and 212 healthy children in a Chinese Han population. Apgar scores and magnetic resonance image scans were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…According to the results, the distribution of NOS3 SNV rs2070744 significantly varied in children with different Apgar scores (≤5, TT/TC/CC = 6/7/5; 6-7, TT/TC/CC = 17/0/0; 8-9, TT/TC/CC = 6/2/0; 10, TT/TC/CC = 7/1/0; p = 0.006). Thus, the NOS3 SNV rs2070744 (p = 0.026) was associated with a high susceptibility to HIE [68].…”
Section: Hypoxic-ischemic Encephalopathy (Hie)mentioning
confidence: 94%
“…According to the results, the distribution of NOS3 SNV rs2070744 significantly varied in children with different Apgar scores (≤5, TT/TC/CC = 6/7/5; 6-7, TT/TC/CC = 17/0/0; 8-9, TT/TC/CC = 6/2/0; 10, TT/TC/CC = 7/1/0; p = 0.006). Thus, the NOS3 SNV rs2070744 (p = 0.026) was associated with a high susceptibility to HIE [68].…”
Section: Hypoxic-ischemic Encephalopathy (Hie)mentioning
confidence: 94%
“…MTHFR polymorphisms were also proposed as biomarkers of brain injury determined using MRI or other imaging methods [ 28 , 29 , 30 ]. Among genes associated with inflammation and oxidative stress, only NOS3 polymorphisms were associated with brain injury on MRI after HIE [ 31 , 32 ], but in these studies, the MRI classification was performed only at two years of age. The association between genetic variability of inflammatory and antioxidant genes and early MRI findings has not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of NOS3 variants on the risk for neurological diseases has been the matter of several recent reports. In this regard, it has been reported an increased risk for delayed cerebral ischemia following aneurismal subarachnoid hemorrhage ( Hendrix et al, 2017 ) and hypoxic-ischemic encephalopathy ( Wu et al, 2016 ). One study in the Iranian population showed an association between NOS3 rs2070744 and multiple sclerosis ( Heidari et al, 2017 ), but this association was not replicated in other populations ( AlFadhli et al, 2013 ; Agúndez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%